Contrastive Graph Learning for Social Recommendation - Zhang, Yongshuai; Huang, Jiajin; Li, Mi; Yang, Jian (Frontiers in Physics, 2022)
Owing to the strength in learning representation of the high-order connectivity of Graph Neural Networks (GNN), GNN-based collaborative filtering has been widely adopted in recommender systems. Furthermore, to overcome the data sparsity problem, some recent GNN-based models attempt to incorporate social information and design contrastive learning as an auxiliary task to assist the primary recommendation task. Existing GNN and contrastive learning based recommendation models learn user and item representations in a symmetrical way, and utilize social information and contrastive learning in a complex manner. Above two strategies result in that these models are either ineffective for datasets with a serious imbalance between users and items or inefficient for datasets with too many users and items. In this work, we propose a Contrastive Graph Learning (CGL) model, which combines social information and contrastive learning in a simple and powerful way. CGL consists of three modules: diffusion, readout and prediction. The diffusion module recursively aggregates and integrates social information and interest information to learn representations of users and items. The readout module takes the average value of user embeddings from all diffusion layers and item embeddings at the last diffusion layer as readouts of users and items, respectively. The prediction module calculates prediction rating scores with an interest graph to emphasize interest information. Three different losses are designed to ensure the function of each module. Extensive experiments on three benchmark datasets are implemented to validate the effectiveness of our model.